Listening in on Multicellular Communication in Human Tissue Immunology - Albers, Julian J.; Pelka, Karin (Frontiers in Immunology, 2022)
Immune responses in human tissues rely on the concerted action of different cell types. Inter- cellular communication shapes both the function of the multicellular interaction networks and the fate of the individual cells that comprise them. With the advent of new methods to profile and experimentally perturb primary human tissues, we are now in a position to systematically identify and mechanistically dissect these cell-cell interactions and their modulators. Here, we introduce the concept of multicellular hubs, functional modules of immune responses in tissues. We outline a roadmap to discover multicellular hubs in human tissues and discuss how emerging technologies may further accelerate progress in this field.